2005
DOI: 10.1128/jb.187.23.8137-8148.2005
|View full text |Cite
|
Sign up to set email alerts
|

Homodimeric Hexaprenyl Pyrophosphate Synthase from the Thermoacidophilic Crenarchaeon Sulfolobus solfataricus Displays Asymmetric Subunit Structures

Abstract: Hexaprenyl pyrophosphate synthase (HexPPs) from Sulfolobus solfataricus catalyzes the synthesis of trans-C 30 -hexaprenyl pyrophosphate (HexPP) by reacting two isopentenyl pyrophosphate molecules with one geranylgeranyl pyrophosphate. The crystal structure of the homodimeric C 30 -HexPPs resembles those of other trans-prenyltransferases, including farnesyl pyrophosphate synthase (FPPs) and octaprenyl pyrophosphate synthase (OPPs). In both subunits, 10 core helices are arranged about a central active site cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 31 publications
5
47
1
Order By: Relevance
“…The dominant roles of the small subunit seem to consist of stabilizing the functional heterodimeric unit of the enzyme through the large hydrophobic interface and directly regulating the product chain length together with the large catalytic subunit HexB. ) previously reported by Sun et al (11). The estimated volume of chain B is probably different from that holding the ligand because the chain is in "open" conformation to release the product (11).…”
Section: Overall Structure Of Ml-hexpps and Structural Comparison-mentioning
confidence: 99%
See 3 more Smart Citations
“…The dominant roles of the small subunit seem to consist of stabilizing the functional heterodimeric unit of the enzyme through the large hydrophobic interface and directly regulating the product chain length together with the large catalytic subunit HexB. ) previously reported by Sun et al (11). The estimated volume of chain B is probably different from that holding the ligand because the chain is in "open" conformation to release the product (11).…”
Section: Overall Structure Of Ml-hexpps and Structural Comparison-mentioning
confidence: 99%
“…The crystal structure of homodimeric Sc-GGPPs revealed that Tyr and His residues located at the bottom of the cleft contacted the -end of the product GGPP and obstructed further chain elongation (PDB code 2E8V) (12). It is widely believed that each subunit of the homodimer in homooligomeric enzymes independently synthesizes the elongated product with a desired chain length (9,11,12,33,37,43). In the case of heterotetrameric Mp-GPPs, the condensation reaction and the C 10 chain length control are essentially dominated only by the large subunit LSU (59).…”
Section: Overall Structure Of Ml-hexpps and Structural Comparison-mentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, mercury can bind to free Cys residues very easily and the phase problem can be easily solved by using at least two mercury datasets by MIR [18][19][20][21]. The mercury atom binding sites were located using AutoSol wizard of PHENIX using 2.4 Å resolution cutoff [22].…”
Section: Structural Determination and Refinementmentioning
confidence: 99%